Unbonded Post-tensioned Precast Concrete Walls With Rocking Connections: Modeling Approaches and Impact Damping - Kalliontzis, Dimitrios; Nazari, Maryam (Frontiers in Built Environment, 2021)
Over the past two decades, precast concrete members have been utilized in seismically resilient structures. In developing these structures, different techniques have been used for connecting the precast members to the foundation. In building construction, unbonded post-tensioning (PT) tendons can anchor a precast wall to the foundation, resulting in the so-called rocking wall system. The rocking wall system develops a dry connection with the foundation and provides moment resistance by means of the PT tendons. The PT tendons remain elastic when the wall is subjected to design-level ground motions to preserve the re-centering capability of the wall. Moreover, the structural damage is concentrated near the wall toes and can be minimized with proper detailing of the toes. Rocking wall systems can consist of a Single precast Rocking Wall (SRW), which uses no supplemental damping, or walls with supplemental damping in the form of viscous or hysteretic energy dissipating devices. In addition to the supplemental damping, rocking walls dissipate the seismic energy through their impacts on the foundation base, their inherent viscous damping, and the hysteresis of concrete near the wall base. While the investigation of rocking walls continues to gain interest, there is no widely accepted means of modeling their dynamic behavior. This paper investigates two popular approaches for modeling rocking walls with and without supplemental damping: the finite element method and analytical modeling. The ability of the two approaches to capture the local and global responses of the walls is evaluated against shake table tests of walls with multiple-level intensity base motions. Next, the behavior characteristics of the two modeling approaches and their ability to simulate impact damping are discussed.